A Newborn Pierre Robin Syndrome Case - Kurt, Ayşegül Neşe Çitak; Yılmaz, Erdal; Kurt, Abdullah; Öcal, Cesur; Aygün, Denizmen (Fırat University, 2007)
Pierre robin sydrome was first reported by Pierre Robin as a triad of mikrognatia, cleft palate, glossopitosis in 1920. It is known that the patient with syndrome have increased risk of a congenital cardiac defects. In this report, we describe a male newborn with cleft palate, mikrognatia glossopitosis and perimembranous ventricular septal defect. Prenatal diagnosis of this syndrome is very difficult. However, postnatal diagnosis can be made simply with a careful physical examination and patients can be scanned with suitable tecnics for anomalies. ©2007, Firat University, Medical Faculty

Pierre Robin sendromu, ilk kez 1920 yılında Pierre Robin tarafından mikrognati, yarık damak, glossopitozdan oluşan üçlü triad olarak tanımlanmıştır. Bu hastalarda konjenital kalp hastalığı görülme riskinin arttığı bilinmektedir. Tanımlanan olgu, yenidoğan erkek hasta, yarık damak, mikrognati, glossopitoz ve perimembranöz ventriküler septal defekti vardı. Sendromun prenatal tanısı zordur. Ancak doğumda yapılan dikkatli bir fizik inceleme ile tanı basit olarak konabilir ve uygun tekniklerle anomaliler açısından taranabilir. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Bir Yenidoğan Pierre Robin Sendromu Olgusu